2019
DOI: 10.3390/w11112264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Irrigation on Biometric Growth, Physiological Response, and Essential Oil of Mentha spicata (L.)

Abstract: A field experiment was performed on spearmint (Mentha spicata L.) under different irrigation regimes in a hilly area of Southern Italy. Objectives of the study include evaluating the physiological and biometrical response of mint from plant establishment up to its complete maturation, as well as the yield composition in essential oil at two different dates. Increasing levels of water stress affected later developing leaves and plant’s water status and net photosynthesis (from the beginning of stress (DAT 63), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Spearmint plants grown in the mountain had significantly higher content of 1,8-cineole, cis-dihydro carvone, neo-dihydro carveol, cis-carveol, dihydrocarveol acetate, and cis-carvyl acetate but lower carvone, and limonene when compared to the plants grown in a plain (Table 10). Carvone was the most abundant spearmint EO constituent in several other reports [109,110], while agronomic factors such as salinity and water stress may affect EOs yield and composition [64,111].…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 93%
“…Spearmint plants grown in the mountain had significantly higher content of 1,8-cineole, cis-dihydro carvone, neo-dihydro carveol, cis-carveol, dihydrocarveol acetate, and cis-carvyl acetate but lower carvone, and limonene when compared to the plants grown in a plain (Table 10). Carvone was the most abundant spearmint EO constituent in several other reports [109,110], while agronomic factors such as salinity and water stress may affect EOs yield and composition [64,111].…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 93%
“…Reference ( 50 ) provides evidence that GC/MS analysis of oil samples can show an increase in thymol content in response to water stress, whereas cymene content decreases. Reference ( 51 ) shows that altering irrigation levels can have significant effects on the quality and quantity of essential oils, impacting various components.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of milder temperatures and higher precipitation volume (Table 1) are likely to be significant contributors to the best performance of plants grown in Pittstown. Higher water availability and ideal ambient temperatures are extensively reported as improving stomatal conductance and net assimilation rates in medicinal and aromatic plants [52,53], and studies with N. cataria demonstrated that the biomass of the plants tends to significantly decrease under low availability of water [25,54].…”
Section: Discussionmentioning
confidence: 99%